2009
DOI: 10.1194/jlr.m800542-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Function and distribution of circulating human PCSK9 expressed extrahepatically in transgenic mice

Abstract: tions in PCSK9 cause hypercholesterolemia in humans ( 1-4 ), whereas loss-of-function mutations in humans lead to a reduction in LDL cholesterol and a marked decrease in the risk of coronary heart disease ( 5-7 ). PCSK9 is a member of the subtilisin serine protease family and the proteinase K subfamily. The protein is synthesized as a proprotein that autocatalytically cleaves to generate mature protein ( 8 ). PCSK9 protein is secreted as a complex containing cleaved N-terminal prodomain, which remains associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 31 publications
7
49
0
Order By: Relevance
“…Although hepatocyte-specific transgenic mice weakly overexpressing PCSK9 (3-fold) exhibit no significant change in circulating LDL-cholesterol, a ϳ30-fold overexpression increased it by ϳ5-fold (20). Data from transgenic mice expressing very high levels of human PCSK9 in mouse kidney (35) or liver (16), or continuous infusions of recipient WT mice with recombinant PCSK9 (36) indicated that Ͼ100 nM amounts of circulating PCSK9 are required to affect liver LDLR protein levels significantly, without affecting extrahepatic LDLR. In that context, we recently showed that annexin A2 inhibits the effect of extracellular PCSK9 on LDLR, and in view of its absence from hepatocytes in vivo, it may exert its inhibitory effect in extrahepatic tissues (14).…”
Section: Discussionmentioning
confidence: 99%
“…Although hepatocyte-specific transgenic mice weakly overexpressing PCSK9 (3-fold) exhibit no significant change in circulating LDL-cholesterol, a ϳ30-fold overexpression increased it by ϳ5-fold (20). Data from transgenic mice expressing very high levels of human PCSK9 in mouse kidney (35) or liver (16), or continuous infusions of recipient WT mice with recombinant PCSK9 (36) indicated that Ͼ100 nM amounts of circulating PCSK9 are required to affect liver LDLR protein levels significantly, without affecting extrahepatic LDLR. In that context, we recently showed that annexin A2 inhibits the effect of extracellular PCSK9 on LDLR, and in view of its absence from hepatocytes in vivo, it may exert its inhibitory effect in extrahepatic tissues (14).…”
Section: Discussionmentioning
confidence: 99%
“…111 In addition, transgenic mice expressing human PCSK9 mainly in the kidney resulted in LDLR degradation mostly in the liver but not in adrenals. 112,113 Thus, it is probable that the high levels of annexin A2 in adrenals are responsible for the refractoriness of the LDLR in this tissue to the action of PCSK9. 110,111 Another, not mutually exclusive, possibility is that in refractory tissues, such as the adrenals, the complex [PCSK9≡LDLR] enters endosomes but does not traffic to lysosomes and may actually recycle back to the cell surface.…”
Section: Adrenals and Kidneysmentioning
confidence: 99%
“…Injection of purifi ed PCSK9 or a recombinant adenovirus overexpressing PCSK9 in mice reduced the protein levels of the LDLR in liver, lung, kidney, and small intestine, but not in the adrenal glands ( 11,12 ). In addition, upon overexpression in kidney, the secreted plasma PCSK9 promotes LDLR degradation mostly in the liver and raises plasma LDL ( 49 ). Altogether, our data and those in the literature show that not all tissues respond equally to local or circulating PCSK9 and that in adult brain LDLR does not respond to circulating PCSK9.…”
Section: Mice During Developmentmentioning
confidence: 99%